Who is afraid of the Gods? Rethinking escapism in Nigerian dramatic literature - Oluwasuji, Olutoba Gboyega (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
Escapism can mean different things to diverse sets of people in various fields of study. To some people, it can mean escape to reality, while some can denote it as an escape to entertainment or distraction from boredom. Escapism in this paper takes a different turn and adopts the term to identify how different decisions can be influenced in any socio-cultural setting. Using South Western Nigeria as a case study, this paper questions the possible interpretations of escapism and the extent to which leaders, especially, identify with them. This paper uses Ahmed Yerima's Sacred Mutters and Iyase to explore the issue of misinterpretation and human machination to escape punishment from the gods. "Sacred Mutters" and "Iyase" highlight leaders' plight before their ascension into power, and the issue of human carelessness, and how he or she is misguided by his or her own intellectual and spiritual interests. The paper argues that modernization and Westernisation had crippled most of the significant and core aspects of African norms, values, and traditions. This degradation has affected the criminal justice system of the people. Against this background, the paper adopts Olawole Famule's connective cultural theory to explore escapism, misinterpretation, and machination in Nigerian discourse. The paper concludes that escapism is the main cause of corruption in the socio-political landscape of Nigeria and calls for a return to traditional African system.